A brief history of equality / Thomas Piketty ; translated by Steven Rendall. - Piketty, Thomas, 1971-; Rendall, Steven, translator (Cambridge, Massachusetts : The Belknap Press of Harvard University Press, 2022)
"In this powerful new work, Thomas Piketty reminds us that rising inequality is not inevitable. Over the centuries, we have been moving toward greater equality. Piketty guides us with elegance and concision through the great movements that have made the modern world and shows how we can learn from them to make equality a lasting reality"--
The movement toward equality: the first milestones -- The slow deconcentration of power and property -- The heritage of slavery and colonialism -- The question of reparations -- Revolution, status, and class -- The "great redistribution": 1914-1980 -- Democracy, socialism, and progressive taxation -- Real equality against discrimination -- Exiting neo-colonialism -- Toward a democratic, ecological, and multicultural socialism.
Includes bibliographical references and index.
Keywords: Social classes -- History